Why do adult women in Vietnam take iron tablets? - Zhao Yun; Nguen Khan C; Jimba Masamine; Aikawa Ritsuko; Binns Colin W; Lee Mi Kyung (BMC, 2006)
Abstract Background Conducting iron supplementation programs has been a major strategy to reduce iron deficiency anemia in pregnancy. However, only a few countries have reported improvements in the anemia rate at a national level. The strategies used for control of nutrition problems need regular review to maintain and improve their effectiveness. The objective of this study was to analyze the factors in compliance with taking iron tablets, where daily doses of iron (60 mg) and folic acid (400 μg) were distributed in rural Vietnamese communes. Methods A cross sectional survey was conducted in Nghe An province, Vietnam in January, 2003. The study population was adult women aged less than 35 years who delivered babies between August 1st 2001 and December 1st 2002 (n = 205), of which 159 took part in the study. Data for the study were collected from a series of workshops with community leaders, focus group discussions with community members and a questionnaire survey. Results Improvements in the rate of anemia was not given a high priority as one of the commune's needs, but the participants still made efforts to continue taking iron tablets. Two major factors motivated the participants to continue taking iron tablets; their experience of fewer spells of dizziness (50%), and their concern for the health of their newborn baby (54%). When examining the reasons for taking iron tablets for at least 5-9 months, the most important factor was identified as 'a frequent supply of iron tablets' (OR = 11.93, 95% CI: 4.33-32.85). Conclusion The study found that multiple poor environmental risk factors discouraged women from taking iron tablets continuously. The availability (frequent supply) of iron tablets was the most effective way to help adult women to continue taking iron tablets.